1982
DOI: 10.3181/00379727-169-41368
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Pineal Melatonin Content during the Estrous Cycle of the Rat

Abstract: Pineal levels of melatonin exhibit a circadian rhythm in the rat. To determine if this rhythm varies during the estrous cycle, adult rats were sacrificed every 2 hr from 2000 hr (prior to lights off) until 0800 hr (2 hr after lights on) throughout each day of the 4-day estrous cycle. Pineal glands were assayed for melatonin by radioimmunoassay. A significant circadian rhythm in the pineal content of melatonin was evident each day of the cycle with peak levels exhibited during the dark phase. There were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 6 publications
2
26
0
2
Order By: Relevance
“…Several reports indicate that, in addition to photoperiod, gonadal steroids influence pineal synthesis or secretion of melatonin (Weiss & Crayton, 1970;Cardinali, Nagle & Rosner, 1974;Ozaki, Wurtman, Alonso & Lynch, 1978;Wilkinson & Arendt, 1978;Johnson, Vaughan, Richardson, Petterborg & Reiter, 1982), although the oestrous cycle does not appear to modify plasma melatonin values in the ewe (Rollag et al, 1978;Arendt étal., 1981). In an investigation into factors controlling pineal melatonin secretion in the ewe we have studied the effect of gonadectomy on plasma melatonin levels during 24 h in different (natural) …”
Section: Introductionmentioning
confidence: 99%
“…Several reports indicate that, in addition to photoperiod, gonadal steroids influence pineal synthesis or secretion of melatonin (Weiss & Crayton, 1970;Cardinali, Nagle & Rosner, 1974;Ozaki, Wurtman, Alonso & Lynch, 1978;Wilkinson & Arendt, 1978;Johnson, Vaughan, Richardson, Petterborg & Reiter, 1982), although the oestrous cycle does not appear to modify plasma melatonin values in the ewe (Rollag et al, 1978;Arendt étal., 1981). In an investigation into factors controlling pineal melatonin secretion in the ewe we have studied the effect of gonadectomy on plasma melatonin levels during 24 h in different (natural) …”
Section: Introductionmentioning
confidence: 99%
“…In the male rat, castration has been shown to reduce both pineal levels of CAMP (19) and the nocturnal elevation of pineal NAT activity (20). In female rats, both pineal melatonin production and release are influenced by the hormonal changes occurring during the rat oestrous cycle (21,22).…”
mentioning
confidence: 99%
“…Whereas pinealectomy or ad ministration of melatonin affects the estrous cycle [15], the specific role of melatonin in the regulation of vaginal cyclicity is not clear. In the albino rat, pineal weight shows a maxi mum at metaestrus [16], and it is reported that melatonin synthesis is elevated during the nights of metaestrus and diestrus [17,18]. The mechanism whereby melatonin alters the duration of metaestrus and influences the in terval between successive stages of the cycle remains unknown.…”
Section: Discussionmentioning
confidence: 99%